Urban green spaces and the influence on vehicular traffic noise control - Lopez, Guillermo Angel Perez (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2018)
In this paper, we explore a statistical relationship between green areas and traffic-related vehicle noise. A medium-sized Brazilian city was selected as the sampling area. This area was divided into 25 subareas and for each subarea a group of descriptors was developed. The parameters considered were the areas occupied by green spaces and the noise pollution index generated by vehicular traffic during day and night periods. The green areas were quantified by digital processing of satellite images. The vehicular traffic noise was measured directly at the site and analysed by the noise pollution index (Lnp), the equivalent sound level (LAeq) and the day/night sound level (Ldn). In order to establish the statistical relationship between noise descriptors and green areas, Pearson's linear correlation coefficient (r) was used. Two analysis types were developed: a generalised one, including the 25 subareas; and a specific one, classifying the subareas into clusters. The first analysis indicated a trend to a medium negative correlation between green areas and noise pollution day index (Lnpd), noise pollution night index (Lnpn) and Ldn (r= -0.577, -0.484, -0.373). In the second analysis, the subarea cluster 3 is considered, which includes areas with clinics and educational institutions. This correlation was classified as high negative (r= -0.729, -0.721, -0.541). The results show indexes with high negative correlation, statistically meaning that there is an inverse proportional relationship between green areas and noise pollution.